Physical Evaluation of Manalagi Apple Extract Mouthwash - Emini Emini; Erwin Erwin; Rini Widiyastuti; Yusmaniar Yusmaniar (Politeknik Kesehatan Kemenkes Jakarta II, 2022)
Manalagi apple (Malus Domestica) is one of the local varieties of apples. Apple rind has benefits such as antibacterial, antioxidant, antifungal, and anti-colliferative. The use of apples needs to be developed in the form of mouthwash products. The aim of the research was to determine the organoleptic evaluation of the manalagi apple peel extract mouthwash formulation. The type of this research was experimental research. The sample in this study was the skin of an apple. The stages in this study were making extracts using the maceration method and making mouthwash formulations of apple peel extracts at concentrations of 25%, 30% and 35%, then organoleptic evaluation was carried out for 4 weeks. The results showed that the organoleptic conditions were the same and stable, namely mint and sweet taste, menthol aroma and no precipitate, and brown color. Based on the results of the study, it was concluded that apple peel extract could be formulated as a mouthwash.